Willingness to accept Covid 19 Vaccines in a Rural Community in Kaduna State, Northwestern Nigeria. (March 2022) - Abubakar, A.A.; Shehu, A.U.; Umar, A.A.; Babandi, Z.; Sokomba, A.; Sadiku, S.; Esekhaigbe, C.E.; Adagba, K.O.; Belgore, S.; Zakka, M.; Saulawa, F.A.
Abstract : Purpose: In Nigeria, rural communities generally have poor access and utilization of health services including immunization services. In rural areas, household heads determine the utilization of health services including immunization. This study was conducted to determine the willingness to accept COVID-19 vaccine among household heads of a rural community in Kaduna State, Northwestern Nigeria. Methods & Materials: A cross-sectional descriptive study was conducted among all household heads in Anguwan Mangu in February 2021 using total population sampling. A pre-tested, electronic based, semi-structured interviewer-administered questionnaire was used for data collection from household heads. Data was analysed using SPSS version 23. Univariate and bivariate analyses were conducted at alpha level of significance set at p< 0.05 Results: Three hundred and thirty-three respondents participated in the study. Age range was 15 to 80 years. Mean age of the respondents was 35 years (±14.45). Only 55% (183/333) of the respondents were willing to accept COVID-19 vaccines. Major reasons for unwillingness to accept vaccines included; didn't feel the need to be vaccinated (4.5%), lack of trust in government (1.8%), belief that vaccine is used for population control (1.8%), belief that COVID-19 is not real (3%), and concerns over safety of the vaccines (1.8%). Household heads less than 50 years were more likely to accept the vaccines than those aged 50 and above (46% vs 41%) (p<0.592), those who were educated were more likely to accept the vaccines (50% vs 46%) (p<0.235), male household heads were more likely to accept vaccines than female household heads (66% vs 48%) (p<0.002). Conclusion: About less than half of the respondents were unwilling to accept the COVID-19 vaccines when available mainly due to misconception about the vaccines. This could pose a major setback in efforts towards controlling the pandemic. It is recommended that Zaria LGA health department should design effective health education intervention strategies based on these misconceptions directed towards enlightening the populace in rural areas in order to improve acceptability of COVID-19 vaccines to fast track the control of the pandemic.